2019
DOI: 10.3390/polym11091385
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Alcohol-Based Deep Eutectic Solvents as Potato Starch Plasticizers

Abstract: The aim of this work was to prepare sugar alcohol-based deep eutectic solvents (DES) and test them as starch plasticizers. Thermoplastic starch (TPS) films were obtained via a simple and convenient thermocompression method. Influence of starch/DES premixtures conditioning (preheating, storage time) on TPS properties was investigated. TPS/sorbitol (S)-based DES exhibited similar tensile strength (TS) (8.6 MPa) but twice higher elongation at the break (ε) (33%) when compared with TPS plasticized only with S. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Some works have used deep eutectic solvents as plasticisers for starch or cellulose to create conductive lms with improved mechanical properties. [20][21][22] Others have used DESs as polymerisation media, e.g. of 2-hydroxyethyl methacrylate 23,24 or poly(ethylene glycol) diacrylate, 25 to obtain eutectogels.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have used deep eutectic solvents as plasticisers for starch or cellulose to create conductive lms with improved mechanical properties. [20][21][22] Others have used DESs as polymerisation media, e.g. of 2-hydroxyethyl methacrylate 23,24 or poly(ethylene glycol) diacrylate, 25 to obtain eutectogels.…”
Section: Introductionmentioning
confidence: 99%
“…However, their toxicity limits their application, [53][54][55] due to the fact that they can be precursors for the formation of carcinogenic compounds for humans such as nitrosamines and nitramines. [56] Novel plasticizers such as low transition temperature mixtures (LTTM) and glycerol and deep eutectic solvents (DES) have shown a good plasticizing effect on starch due to the fact that they exhibit less hygroscopicity, [57] can generate crosslinking with the polysaccharide, [44] and obtain more amorphous materials. [49] Studies reported by other authors have identified and made the most of the advantages offered by mixtures of different plasticizers, to the fore being glycerol-sorbitol, [7,51,58] ureaethanolamine, [59] urea-formamide, [60] and sugars-glycerol.…”
Section: Plasticizers For Tpsmentioning
confidence: 99%
“…Although a large number of substances with which to plasticize starch have been studied, [25,41,57,[61][62][63][64] reporting good results in thermoplastic materials obtained by extrusion, much of the field awaits exploration. New plasticizers that have been tested by compression molding or casting could have great application potential using extrusion.…”
Section: Plasticizers For Tpsmentioning
confidence: 99%
See 2 more Smart Citations